The Landscape Perception as Pasemon Artistic in Wayang Kayon Figure - Pandu Pramudita; Sarwanto Sarwanto; Soetarno Soetarno; Dendi Pratama (Mudra Jurnal Seni Budaya, 2023)
Wayang Kayon filling is often understood as an ornament that is interpreted separately. The fillings are composed in such a way that they interact. The interaction between Wayang Kayon fillings forms landscape perception. This study aims to explain landscape perception in Wayang Kayon figures. The theory used to explain the landscapes depicted on Wayang Kayon figures is the perception theory. This research uses qualitative methods with an interpretive-iconographic approach. The Wayang Kayon filling is three composed layers of the structure, including pucukan, genukan, and lengkeh. The filling found on the pucukan Wayang Kayon is a tree of life form that is the landscape perception as mountain and forest. The filling of the genukan and lengkeh on the Wayang Kayon Blumbangan figure shows the ponds, animals, plants, and/or mythological creatures formation that are the landscape perception as an ecosystem around a water source. The filling of the genukan and lengkeh on the Wayang Kayon Gapuran figure shows the gate formation that is the landscape perception as a landscape of sacred buildings. Wayang Kayon filling is depicted through pasemon artistic concept so that it is understood as native art. This research is expected to be a guide for shadow puppet spectators to understand the Wayang Kayon figures filling and for shadow puppet artists to pay attention to the Wayang Kayon filling results creations so that the interaction between fillings still perceives the landscape.